On the Problem of the "Huns-Sarmatians" - Symonenko, Oleksandr (Anabasis. Studia Classica et Orientalia, 2012)
In the culture of the Sarmatians from the 2nd c. BC till the early 2nd c. AD we can discern some cultural features that are similar to the South Siberian Pazyryk, Xiongnu and Chinese cultures. Elements of these cultures found in the areas occupied by the Sarmatians are usually explained by trading and cultural links along the Great Silk Road, without any special exploration of the concrete mechanism of these links. The integration of all these elements into the culture and art of the Alans could hardly be connected with the trade along the Great Silk Road – such objects were not traded. Rather, it appears that the Alans lived in close contact with the Xiongnu and Chinese for a long time, and in this way their culture was enriched with the borrowings listed above. All these innovations appeared simultaneously in Eastern Europe in the middle of the 1st century AD in the archaeological area identified as Alanian. Analysis of this material allows us to consider that the Alans acquired Chinese and Xiongnu items while still in their more easterly homeland, a location that, until now, had not been unequivocally determined. The Pazyryk, Chinese and Xiongnu elements in the Alanian culture also allow us to assume that the Alans were the successors of the Pazyryk people who lived among the Xiongnu or in the near vicinity for a long time and, as well as Xiongnu, experienced the strong influence of Chinese culture. This was most likely somewhere in the territory of modern Western Mongolia or Xingjian. In the middle of the 1st century AD the Alans moved westward and very quickly reached the Sarmatian lands in Eastern Europe.